Optimizing The Role of Posyandu Cadres Through Growth Monitoring Training and Nutrition Education for The 1000 HPK Day As An Efforts to Prevent Stunting: Optimalisasi Peran Kader Posyandu Melalui Pelatihan Pemantauan Pertumbuhan dan Edukasi Gizi 1000 HPK Sebagai Upaya Pencegahan Stunting - Sari, Diesna; Mayangsari, Riska; Dwirizky Abdullah, Anisa (Jukeshum: Jurnal Pengabdian Masyarakat, 2025)
Stunting is a growth and development disorder experienced by children due to chronic nutritional deficiencies, one of the causes of which is inadequate nutrition and repeated infections during the first 1000 days of a child's life. Acceleration in reducing stunting can be done by optimizing existing resources, one of them is by optimizing the role of posyandu cadres through growth monitoring training and education related to nutritional fulfillment during 1000 HPK. This community service activity aims to improve the competence of cadres in early detection of stunting and understanding the importance of 1000 HPK in preventing stunting. The method of implementing community service is carried out in 3 stages, namely the preparation, implementation and evaluation stages. The educational media used are in the form of slideshows and leaflets. The evaluation of this community service activity is through the provision of a pre-post test questionnaire. From the results of the activity evaluation, the knowledge of cadres has increased after participating in toddler growth monitoring training and 100 HPK nutrition education. Empowerment of posyandu cadres in the form of increasing knowledge or training provided can improve the knowledge, skills, and motivation of cadres to play an active role in preventing or overcoming stunted toddlers in Indonesia.